Analysis of the Principal's Level of Financial Management Understanding in Enhancing Facilities and Infrastructure - Baharuddin; Mardhiah Hasan; Dodi Ilham Mustaring; Nur Husnul Khatimah; Kurniawan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This research evaluates the principal's understanding of financial management and its direct impact on improving facilities and infrastructure at SMA Negeri 1 Palopo. Using a quantitative research approach, the study reveals that the principal’s understanding of financial management falls within the medium category, with an average score of 57.75. This indicates a fairly good comprehension but highlights the need for optimization. Meanwhile, the adequacy level of school facilities and infrastructure is rated at 51.92%, which, although classified as sufficient, still requires improvement. The findings emphasize a direct correlation between financial management understanding and the quality of school facilities. Effective financial management allows for better allocation of resources, ensuring that funds are utilized efficiently to enhance infrastructure. However, challenges such as limited human resources and budget constraints hinder progress. Managerial focus on the quality and suitability of school facilities plays a crucial role in bridging this gap. Therefore, strengthening financial literacy among school leaders can lead to more strategic planning and improved infrastructure development. This study underscores the necessity of enhancing financial management skills to maximize available resources, ultimately fostering a better learning environment through improved school facilities. These insights offer valuable directions for policy improvements and future educational management strategies